Biofilm-responsive encapsulated-phage coating for autonomous biofouling mitigation in water storage systems. (1st October 2022) - Zuo, Pengxiao; Metz, Jordin; Yu, Pingfeng; Alvarez, Pedro J.J.
Highlights: Chitosan was crosslinked to form a pH-responsive encapsulation for phages. Phage release is triggered by the acidic pH of biofilm inner layers. Phage release occurs only when needed for bottom-up biofilm attack. Encapsulated phages are easily coated on water storage tank surface materials. This chemical-free approach mitigated Pseudomonas aeruginosa biofilms. Abstract: Biofilms in water storage systems may harbor pathogens that threaten public health. Chemical disinfectants are marginally effective in eradicating biofilms due to limited penetration, and often generate harmful disinfection byproducts. To enhance biofouling mitigation in household water storage tanks, we encapsulated bacteriophages (phages) in chitosan crosslinked with tri-polyphosphate and 3-glycidoxypropyltrimethoxysilane. Phages served as self-propagating green biocides that exclusively infect bacteria. This pH-responsive encapsulation (244 ± 11 nm) enabled autonomous release of phages in response to acidic pH associated with biofilms (corroborated by confocal microscopy with pH-indicator dye SNARF-4F), but otherwise remained stable in pH-neutral tap water for one month. Encapsulated phages instantly bind to plasma-treated plastic and fiberglass surfaces, providing a facile coating method that protects surfaces highly vulnerable to biofouling. Biofilm formation assays were conducted in tap water amended with 200 mg/L glucose to accelerate growth and attachment of Pseudomonas aeruginosa, an opportunistic pathogen commonly associated with biofilms in drinking water distribution and storage systems. Biofilms formation on plastic surfaces coated with encapsulated phages decreased to only 6.7 ± 0.2% (on a biomass basis) relative to the uncoated controls. Likewise, biofilm surface area coverage (4.8 ± 0.2 log CFU/mm 2 ) and live/dead fluorescence ratio (1.80) were also lower than the controls (6.6 ± 0.2 log CFU/mm 2 and live/dead ratio of 11.05). Overall, this study offers proof-of-concept of a chemical-free, easily implementable approach to control problematic biofilm-dwelling bacteria and highlights benefits of this bottom-up biofouling control approach that obviates the challenge of poor biofilm penetration by biocides. Graphical abstract: Image, graphical abstract .